Effect of Addition Pediococcus acidilactici Bacteria and Time of Growth in Dissolved Protein of Earthworm Extract - Purba, Hanna Permatasari (Journal of Food and Life Sciences, 2017)
Earthworm (L.rubellus) has a high nutrient that can be used as a medium to grow microorganisms replacing pepton or meat ekstak. To deermine the function then tested on Pediococcus bacteria. Pediococcus bacteria is a probiotic bacterium that has protease activity that is expected to maintain and increase dissolved protein content with increasing growth time. This study aims to determine the addition of bacterial starter and microbial growth time during fermentation to the best value of dissolved protein content from earthworm extract. The experimental design used in the form of Nested Design consists of the addition of Pediococcus acidilactici bacteria starter and without addition of bacterial starter with Growth Time of 2 days, 4 days and 6 days. The result of this research is the best value of dissolved protein content of earthworm extract with addition of bacteria starter at growth time during 2 day fermentation that is equal to 1,26%.Keywords: Earthworm, Pediococcus acidilactici, Dissolved Protein